The Effectiveness of Role-Playing Intervention as a Behavior Modification Strategy to Reduce Off-Task Behavior in Kindergarten Students - Esmiati, Amy Novalia (Psikologi Prima, 2025)
Off-task behavior in early childhood is a significant challenge in the learning process that can impede academic achievement and social-emotional development. This research aims to examine the effectiveness of role-playing intervention as a behavior modification strategy to reduce off-task behavior in Kindergarten students. The study uses a descriptive qualitative approach with a psychological assessment-intervention method involving 7 children from group B2 (aged 6-7 years) at TK Aisyiyah 52 Jebres, Surakarta. Research data were analyzed using thematic analysis. The results indicate an improvement in focus, cooperation, and task completion abilities. These findings confirm that role-playing combined with teacher counseling and reinforcement is an effective approach for early childhood behavior modification. This research provides a practical contribution in the form of an intervention guide that can be replicated by Early Childhood Education teachers in addressing off-task behavior issues in the classroom.